2021
DOI: 10.1002/jcb.30109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of potential inhibitors and targeting fat mass and obesity‐associated protein causing diabesity through docking and molecular dynamics strategies

Abstract: Genome-wide association studies (GWAS) have identified an association between polymorphisms in the FTO gene and obesity. The FTO: rs9939609, an intronic variant, is considered a risk allele for developing diabesity in homozygous and heterozygous forms. This study aimed to investigate the molecular structure of the available inhibitors specific to the FTO mutations along with the rs9939609 variant. We identified the best-suited inhibitor molecules for each mutant type containing the rs9939609 risk allele. Misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…In clinical trials, PI3Kα and PIK3δ inhibitors, as well as AKT inhibitors, are being utilized to treat ER‐positive BC patients with PIK3CA mutations. The comparison of protein‐ligand interaction using molecular docking and dynamics studies was previously reported in several proteins responsible for cancer and genetic diseases 99,101 . Extrinsic events such as hypoxia, oxidative stress, and acidosis, as well as intrinsic factors such as MYC amplification, PIK3CA, and TP53 mutations (Supporting Information: Figure S4), all lead to various metabolic reprogramming patterns in metastatic breast tumors.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In clinical trials, PI3Kα and PIK3δ inhibitors, as well as AKT inhibitors, are being utilized to treat ER‐positive BC patients with PIK3CA mutations. The comparison of protein‐ligand interaction using molecular docking and dynamics studies was previously reported in several proteins responsible for cancer and genetic diseases 99,101 . Extrinsic events such as hypoxia, oxidative stress, and acidosis, as well as intrinsic factors such as MYC amplification, PIK3CA, and TP53 mutations (Supporting Information: Figure S4), all lead to various metabolic reprogramming patterns in metastatic breast tumors.…”
Section: Resultsmentioning
confidence: 93%
“…The comparison of protein-ligand interaction using molecular docking and dynamics studies was previously reported in several proteins responsible for cancer and genetic diseases. 99,101 Extrinsic events such as hypoxia, oxidative stress, and acidosis, as well as intrinsic factors such as MYC amplification, PIK3CA, and TP53 mutations (Supporting Information: Figure S4), all lead to various metabolic reprogramming patterns in metastatic breast tumors. The functions of PIK3CA and TP53 in cancer and treatment resistance have been the subject of research; however, their interactions and potential involvement in promoting cancer hallmarks have received much less attention.…”
Section: P53 Pathwaymentioning
confidence: 99%
“…The remaining hit molecules showed an average (~1–3) H‐bonds (Figure 6B). As the protein functions through cumulative atomic motions, the PCA 10,49–51 study was employed to understand the movements of the Cα atoms structurally for the five complexes. Based on the cumulative motion of the complexes, the first and last principal components were employed to construct the PCA graph.…”
Section: Resultsmentioning
confidence: 99%
“…Discovering potent inhibitors with a restricted number of studies would pose a challenge [82]. According to the literature, molecular modeling and molecular dynamics simulations are highly effective in reducing the number of potential FTO inhibitors while still being computationally efficient [83]. Drug virtual screening has a lengthy and extensive history, encompassing the development of various related techniques like docking, Quantitative Structure Activity Relationship (QSAR), pharmacophore, and structure-based ligand similarity [84].…”
Section: Discussionmentioning
confidence: 99%